Innovative methodological model of instrumental preparation of future teachers of musical art in the aspect of development of their performing independence - Burnazova, Vira (ScienceRise: Pedagogical Education, 2020)
The development of performing independence of future teachers of musical art as non-innate but acquired integral property of a personality is considered, which contributes to a high level of reproducing the necessary information, based on the creative embodiment of the original interpretational model of musical works into the process of instrumental activity. The developed methodological bases of its four-phase development are offered. The first phase is characterized by the direction of students' efforts to establish the internal organization of the motives and impulses of the will to realize incentive actions for obtaining objective information about the real assessment of the stage-interpretative complexity of musical works in the course of familiarization with the general features of their textual and performing components. The second phase involves activating the aspirations of students to give priority to procedural motivation, which contributes to the maximum depth in the process of awareness of musical information, the integration and automation of play movements in order to concretize the features of the interpretation model of musical works. In the third phase, priority is given to encouraging students to maintain the attractiveness of the installations during their rehearsal realization, and in the fourth – their orientation to consolidate the achieved executive autonomy by emotionality of the conditions of stage activity. The introduction of an appropriate innovative methodological model in the system of instrumental training of future teachers of music arts, will help to resolve the issues of optimization of vocational training directions, stimulating self-employment, which undoubtedly influences the formation of demotivating indicators for reducing labor migration from Ukraine